Shifting the paradigm in community-based water resource management in North-West Cameroon: A search for an alternative management approach. Issue 2 (14th March 2020) - Tantoh, Henry Bikwibili; Simatele, Mulala Danny; Ebhuoma, Eromose Ehije
ABSTRACT: This paper examines practical approaches for Community-Based Water Resource Management in North-West Region, Cameroon. Empirical data collected through participatory learning and action revealed that a lesser degree of community involvement and more centralized systems of Natural Resource Management (NRM), is a major cause of unsustainable water management. A fundamental challenge in NRM is how to effectively engage and stimulate public, private and local institutions in policymaking to address resource use conflicts and improve governance. Part of the problem in developing effective management models has been identified through the nature of approaches that inform contemporary methodologies of NRM. Many of these methods have largely been influenced by top-down systems of management that have played a major role in disenfranchising those for whom development is meant for. It is, therefore, imperative to rethink contemporary management approaches and develop more pragmatic models that will promote effective systems of NRM. A focus on and applying a rational System Thinking Analysis could potentially produce reinforcing and self-reinforcing effects to enhance rural water systems and promote sustainable water management in the North-West Region, Cameroon.